Levels of Historical Consciousness and Appreciation of Local Cultural Heritage among Grade 8 Students in Lucena City - Buo, Mark Culla; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2025)
This research explored the levels of historical consciousness and appreciation for local cultural heritage among Grade 8 students from Lucena City and established the relationship between the two variables. A descriptive-correlational design was utilized with 128 students (20% of the entire Grade 8 population) at Lucena City National High School for the school year 2024–2025. Stratified random sampling was used to guarantee proportional representation from 14 sections. Data were collected through a validated 4-point Likert scale questionnaire assessing four dimensions of historical consciousness—knowledge of local history, understanding of local context, critical thinking skills in history, and connection to the past—and four dimensions of appreciation of local cultural heritage—knowledge of cultural practices, engagement with local cultural heritage, attitudes toward cultural heritage, and perceived value of cultural heritage. Descriptive statistics encapsulated the levels of both variables, and Pearson's correlation coefficient was used to test the relationship at a 0.01 significance level. Students showed overall high historical consciousness, and